Development of a Canva-Based Toddler Nutrition E-Module in Applied Nutrition Courses - Zakiah, Azzahra; Nur Riska; Rusilanti (Jurnal Sains Boga, 2024)
This research aims to: 1) Develop Canva-based toddler nutrition e-module teaching materials and 2) Assess the feasibility of Canva-based toddler nutrition e-module teaching materials. This teaching material was developed using the Research and Development method with the ADDIE development model. The stages of this research consist of five stages, namely analysis, design, development, implementation and evaluation. Research data was collected using a questionnaire and analyzed descriptively qualitatively. The results of the research show that Canva-based toddler nutrition e-module teaching materials are considered "Very Appropriate" by material experts with a percentage of 89%, by media experts with a percentage of 83% which is in the "Very Appropriate" category, and by language experts with a percentage of 100% which is falls into the "Very Decent" category. Product trials are carried out in three stages, namely one-on-one trials, small group trials and field trials. The results of the one-on-one trial assessment showed a feasibility level of 92% (very feasible), the results of the small group trial assessment were 85% (very feasible), and the results of the field trial assessment were 83% (very feasible).